Serious, Violent, and Chronic Prison Misconduct: Are the Predictors the Same for Women and Men? - Logan, Matthew W. (The prison journal, 2023)
Inmate misconduct is a focal concern among those who live and work in prisons, and is committed primarily by a few offenders with discernable backgrounds. The current study examines the most prolific rule violators (the top 1 and 10%) among a large sample of inmates housed across Ohio correctional facilities. We focus on the characteristics that predict membership into these categories and whether differences in their rates of occurrence exist between males and females. Findings show more similarities than differences between groups. Implication for theory and practice are discussed, as well as suggestions for future research.